Mechanism of activation of the human trk oncogene. - Coulier, F (1989)
The human trk oncogene was generated by a genetic rearrangement that replaced the extracellular domain of the normal trk tyrosine kinase receptor by sequences coding for the 221 amino-terminal residues of a nonmuscle tropomyosin. Molecular dissection of a cDNA clone of the trk oncogene indicated that both the tropomyosin and tyrosine kinase domains were required for proper transforming activity. Replacement of nonmuscle tropomyosin sequences with those of other tropomyosin isoforms had no deleterious effect. However, when tropomyosin sequences were replaced with those of another cytoskeletal gene, such as beta-actin or beta-globin, transforming activity was completely abolished. These results illustrate the important role of tropomyosin sequences in endowing the trk kinase with transforming properties. Functionally unrelated subdomains of the tropomyosin molecule were equally efficient in activating the trk gene. Moreover, the transforming activity of the trk oncogene was not affected when its subcellular localization was drastically altered. Therefore, tropomyosin sequences are likely to contribute to the malignant activation of the trk oncogene not by facilitating its interaction with defined cytoskeletal structures as initially suspected, but by allowing its kinase domain to fold into a constitutively active configuration.